Assessment of the nematocidal activity of metallocenyl analogues of monepantel. Issue 44 (17th October 2016) - Hess, Jeannine; Patra, Malay; Jabbar, Abdul; Pierroz, Vanessa; Konatschnig, Sandro; Spingler, Bernhard; Ferrari, Stefano; Gasser, Robin B.; Gasser, Gilles
Abstract : Ferrocenyl and ruthenocenyl analogues of the nematocidal drug monepantel show organometallic-dependent activity against Haemonchus contortus and Trichostrongylus colubriformis . Abstract : In this study, we present the design, synthesis, characterization and biological evaluation of structurally new ferrocenyl and ruthenocenyl derivatives of the organic anthelmintic monepantel (Zolvix ® ). All seven metallocenyl derivatives prepared (4a /b, 5a /b, 6a /b and7 ) were isolated as racemates and characterized by 1 H, 13 C and 19 F NMR spectroscopies, mass spectrometry, IR spectroscopy and elemental microanalysis. The molecular structures of four compounds (4a /b, 6a and7 ) were further confirmed by X-ray crystallography. The biological activities of the organometallic intermediates (4a /b ) and organometallic derivatives of monepantel (5a /b, 6a /b and7 ) were evaluated in vitro using parasitic nematodes of major importance in livestock, namely Haemonchus contortus and Trichostrongylus colubriformis . Two ferrocenyl compounds (4a and6a ) showed nematocidal activity, while the analogous ruthenocenyl compounds (4b and6b ) were not active at the highest concentration tested (10 μg mL −1 ). In order to obtain insight into the difference in activity between ferrocenyl and ruthenocenyl derivatives, the potential of the compounds for reactive oxidative species (ROS) production in live cells was assessed. Interestingly, neither the ferrocenyl nor the ruthenocenyl compounds (4a /b and6a /b ) produced significant ROS in HeLa cells when checked after 22 h, potentially indicating a redox-independent activity of4a and6a on the parasites. The selectivity of the compounds on parasites was confirmed by investigating their cytotoxicity profiles. None of these compounds was toxic either to HeLa or MRC-5 cells. Thus, 4a and6a could be considered as interesting leads for further development of new classes of anti-parasitic agents.